2019
DOI: 10.1186/s13049-019-0632-4
|View full text |Cite
|
Sign up to set email alerts
|

Live video footage from scene to aid helicopter emergency medical service dispatch: a feasibility study

Abstract: Background Obtaining accurate information from a 112 caller is key to correct tasking of Helicopter Emergency Medical Services (HEMS). Being able to view the incident scene via video from a mobile phone may assist HEMS dispatch by providing more accurate information such as mechanism of injury and/or injuries sustained. The objective of this study is to describe the acceptability and feasibility of using live video footage from the mobile phone of a 112 caller as an HEMS dispatch aid. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 12 publications
2
44
0
1
Order By: Relevance
“…Novel approaches which review call communication and conversation analysis between the caller or bystander and call taker may allow us to identify unknown criteria missing from reviews of dispatch accuracy. Similarly, live video-transmission from scene may help gauge physiological parameters and expedite dispatch [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Novel approaches which review call communication and conversation analysis between the caller or bystander and call taker may allow us to identify unknown criteria missing from reviews of dispatch accuracy. Similarly, live video-transmission from scene may help gauge physiological parameters and expedite dispatch [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…These efforts may increase bystander CPR rates and decrease time to first compression and defibrillation. Additionally, this may be complemented by videoassisted dispatching, as has been trialed by GoodSAM [28]. While this implementation focused on the remote initial assessment of trauma, studies have shown that video-assisted dispatching may improve the quality of DACPR provided compared to the current, audioinstructed method [29].…”
Section: Future Developmentsmentioning
confidence: 99%
“…However, no combination of clinical criteria alone is perfect. Novel approaches focussing on communication in the initial call [ 20 ] and live video transmission from scene [ 21 ] may help to identify patients needing HEMS interventions earlier.…”
Section: Discussionmentioning
confidence: 99%